Study of Internal Flow in Open-End and Closed Pressure-Swirl Atomizers with Variation of Geometrical Parameters - Ronceros, Julio (2023)
This study delves into the examination of internal flow characteristics within closed (with nozzles) and open-end pressure-swirl atomizers (lacking nozzles). The number of inlet channels “n” and the opening parameter “C” were manipulated in this study, as they play a pivotal role in understanding various atomizer attributes, such as uniformity of the air-core diameter, the discharge coefficient, spray angle, and more, all of which hold significance in the design of bipropellant atomizers for liquid rocket engines (LREs). To validate our findings, six distinct hexahedral meshes were generated using Ansys ICEM software 2023. Subsequently, we employed Ansys Fluent, considering the RNG k-ε turbulence model and the VOF (volume-of-fluid) multiphase model to identify the liquid–gas interface, to aid in analyzing the uniformity of the air core, which is directly linked to the even distribution of mass, the mixing ratio of propellants, combustion efficiency, and stability. The results indicate that the uniformity of the air core is not solely contingent on an increase in parameter “n” but is also influenced by an increase in the parameter “C”. It is worth noting that the key dimensions of these six atomizers were determined using a mathematical model based on Abramovich and Kliachko theories.